The Effect Of Transformational Leadership And Organizational Culture On Police Performance Mediated By Job Satisfaction In Aceh Tamiang Resort Police - Bahdin Nur Tanjung; Hazmanan Khair; Fauzan Lisawadi; Larasati Nur Kharomah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research investigates the impact of transformational leadership and organizational culture on police performance at the Aceh Tamiang Police Department. It examines whether job satisfaction mediates this relationship. The research utilizes an associative approach and involves all Aceh Tamiang Police personnel as the population. A stratified random sample of 96 personnel was selected for the study. Transformational leadership variable and organizational culture variable serve as independent variables, while police performance variable is the dependent variable. Job satisfaction acts as an intervening variable. Data analysis employs descriptive analysis and Structural Equation Modelling, with a Partial Least Squares approach. The findings demonstrate a positive effect of transformational leadership and organizational culture on police performance. This effect operates both directly and indirectly through increased job satisfaction among police officers. It means that a transformational leadership style and positive organizational culture can increase members' job satisfaction, ultimately impacting their performance. In other words, to improve the performance of police officers, efforts need to be made to increase the transformational leadership of leaders and strengthen a positive organizational culture.